Hypertensive elderly people: assessing the quality of life - Larissa Cristina Rodrigues Alencar; Ana Hélia de Lima Sardinha (Universidade Estadual de Maringá, 2019)
The objective of the present study was to evaluate the quality of life in hypertensive elderly people assisted in the Family Health Strategy. This is a descriptive, exploratory, cross-sectional study, with quantitative approach. The participants were 544 hypertensive elderly patients. The instruments used for data collection were the sociodemographic form and the WHOQOL-BREF. Regarding the socioeconomic and demographic characteristics of the elderly participants of this study, there was prevalence of elderly women, aged 60-69 years, self-reported white, catholic religion, illiterates, coming from municipalities in the countryside of the state, married/stable union, retired, income of one minimum wage, with children, non-smokers, non-alcohol consumers. Regarding the quality of life, the highest score was obtained in the Social Relationships Domain, followed by the Psychological Domain, Physical Domain and lower score in the Environmental Domain. The results show that the elderly participants presented a good quality of life and, although they have high blood pressure levels, they seek to live as best as possible.